Compositional Analysis of Flatworm Genomes Shows Strong Codon Usage Biases Across All Classes - Lamolle, Guillermo; Fontenla, Santiago; Rijo, Gastón; Tort, Jose F.; Smircich, Pablo (Frontiers in Genetics, 2019)
In the present work, we performed a comparative genome-wide analysis of 22 species representative of the main clades and lifestyles of the phylum Platyhelminthes. We selected a set of 700 orthologous genes conserved in all species, measuring changes in GC content, codon, and amino acid usage in orthologous positions. Values of 3rd codon position GC spanned over a wide range, allowing to discriminate two distinctive clusters within freshwater turbellarians, Cestodes and Trematodes respectively. Furthermore, a hierarchical clustering of codon usage data differs remarkably from the phylogenetic tree. Additionally, we detected a synonymous codon usage bias that was more dramatic in extreme GC-poor or GC-rich genomes, i.e., GC-poor Schistosomes preferred to use AT-rich terminated synonymous codons, while GC-rich M. lignano showed the opposite behavior. Interestingly, these biases impacted the amino acidic usage, with preferred amino acids encoded by codons following the GC content trend. These are associated with non-synonymous substitutions at orthologous positions. The detailed analysis of the synonymous and non-synonymous changes provides evidence for a two-hit mechanism where both mutation and selection forces drive the diverse coding strategies of flatworms.